Risk of Bias and Quality of Evidence for Treatment of ADHD With Stimulant Medication. Issue 4 (4th September 2018) - Swanson, James M.
Abstract: Storebø et al . provide a concise summary of two Cochrane reviews about benefits and harms of treatment of attention‐deficit/hyperactivity disorder (ADHD) with methylphenidate: (1) a review of 185 randomized controlled trials that estimated benefits (e.g., moderate‐to‐large reduction in teacher‐rated ADHD symptoms) and (2) a review of 260 nonrandomized trials that estimated harms (e.g., infrequent serious but frequent nonserious adverse events). They also mention (without providing much detail) additional information from the structured Cochrane method about the risk for bias in the trials reviewed (assessed as being high) and quality of evidence of the outcomes considered (rated as being very low). This led to the conclusion that "the jury is still out on benefits and harms." A similar conclusion of the first review generated an extensive debate in the literature. Some details will be summarized and discussed herein to provide context in case the recent review and the summary by Storebø et al . revive the debate.